Public knowledge, attitude and practice toward diabetes mellitus in Hail region, Saudi Arabia - Aljofan M; Altebainawi A; Alrashidi MN (International Journal of General Medicine, 2019)
Mohamad Aljofan,1 Ali Altebainawi,2–4 Mubarak Nsha Alrashidi21Department of Biomedical Sciences, Nazarbayev University School of Medicine, Astana 010000, Kazakhstan; 2Pharmacy College, Hail University, Hail, Kingdom of Saudi Arabia; 3Aja Pharmaceutical Industries Co. Ltd, Riyadh, Saudi Arabia; 4Medication Safety Research Chair - KSU, Riyadh, Saudi ArabiaBackground: There is a rapid increase in the number of people with type II diabetes worldwide with many preventable cases. Diabetes control or prevention is partially influenced by the individual’s knowledge, attitude and practice toward the disease.Objective: The aim of this study was to determine the general public knowledge, attitude and practice toward diabetes in the region of Hail, which is located northern of the Saudi capital.Methodology: This is a cross-sectional study conducted during the period of March 2018 until September 2018. We randomly selected participants over the age of 18 years at different locations.Results: A total of 738 participants (428 females and 310 males) with and an age range of 18–61 years and mean age of 35±12 were surveyed. The majority of the participants, regardless of education levels, residence and employment status showed high knowledge of diabetes (82%) and knew that physical activity can positively affect/prevent diabetes. Participant’s age was found to have a significant association with participant’s knowledge of diabetes with the ≥35 year old group knew the different types of diabetes (p<0.001) and knew that high carbohydrate consumption can increase the risk of diabetes (p<0.001), but only the younger group <18 year old’s identified diabetes as a genetic disorder (p<0.001).Conclusion: The high knowledge of the disease and its risk factors were not truly mirrored in the participant’s attitude and practice toward the disease. Therefore, it is quite essential for the local health authorities to implement awareness programs to improve public attitude and practice toward diabetes.Keywords: knowledge, attitude, practice, diabetes mellitus, general population